Low stroke volume during exercise with hot skin is due to elevated heart rate - Chou, T. H.; Akins, J. D.; Crawford, C. K.; Allen, J. R.; Coyle, E. F. (Medicine & Science in Sports & Exercise, 2019)
It is well known that hyperthermia lowers stroke volume (SV) during moderate-intensity prolonged exercise, yet the underlying mechanism is inconclusive, especially when skin temperature (Tsk) is hot (=38°C).